KESELARASAN ISLAM DAN SAINS - David, Abadi; Yahya, Yulia Putra (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2024)
This article tries to review the relationship between religion and science.There are several opinions regarding the relationship between the two.There are those who believe that religion and science are in conflict with each other.There are also those who say that religion and science are in harmony and even strengthen each other.However, this article will strengthen the opinion that religion and science are in harmony with each other.The collection method in this paper is literature study.The data source in this paper are book,journals,and other related literature.This article present several facts that islam and science are in harmony and even strengthen each other.Islam is in harmony with science, this is proven by the harmony of the verses of the al-qur’an , as the main source of islam